Performance of independent horizontal and inclined bars as shear reinforcement for reinforced concrete beams - Abdul Hamid, Noor Azlina; Abdullah, Ramli; Adnan, Suraya Hani; Jamellodin, Zalipah; A. Majid, Masni; Salleh, Norhafizah; Md. Noor, Nurazuwa (Institute of Advanced Scientific Research, 2020)
This paper presents an experimental results of concrete beams reinforced with new shear reinforcement design of using independent horizontal and inclined bars. A total of six beams, measuring 200 mm width x 250 mm height x 2300 mm length were tested up to failure under four-point loading. The effectiveness of using independent horizontal and inclined bars to the shear carrying capacity of the beam was investigated. The independent horizontal and inclined bars with reinforcement ratios between 1.0% and 2.9% were provided in reinforced concrete beams. All the beams were cast with normal grade of concrete compressive strength between 30 to 35 MPa. The performance of the tested beams in terms of ultimate load, mid-span deflection and crack patterns were recorded and compared. The test results showed that beams reinforced with independent horizontal and inclined bars of 1.9% and 2.9% experienced higher shear load capacities than beams with conventional shear reinforcement system. It can be concluded that the use of independent horizontal and inclined bars as shear reinforcement gives good shear resistant for the beams. Furthermore, these types of shear reinforcement system are more flexible, simple which significantly reduced the congestion of vertical links within shear span zone.